Therapeutic Effects and Mechanism of Panax ginseng in Improving Spermatogenesis: Evidence from Network Pharmacology and Molecular Docking - Tran, Nhat Minh; Hoang, Thi Ai Phuong; Dang, Ngoc Phuc; Nguyen, Thanh Tung (Tạp chí Y Dược Huế, 2024)
Background: Spermatogenesis is a complex process involving mitotic cell division, meiosis, and spermiogenesis. This study aimed to examine the therapeutic effects and mechanisms of Panax ginseng in improving spermatogenesis, using a systematic network pharmacology approach and molecular docking. Methods: Traditional Chinese Medicine Systems Pharmacology (TCMSP) and Herbal Ingredients’ Targets (HIT) databases were used to screen for bioactive compounds in Panax ginseng. The SwissTargetPrediction, BATMAN-TCM, HIT, and TCMSP databases were used to identify and obtain the targets. The OMIM database and GeneCards Version 5.20 were searched to obtain targets related to spermatogenesis. The protein-protein interaction (PPI) network was constructed using common targets from the Search Tool for the Retrieval of Interacting Genes/Proteins (STRING) database. The DAVID tool was used for Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis. AutoDock Vina software was used for molecular docking analysis. Results: A total of 250 overlapping target genes were identified in Panax ginseng and during spermatogenesis. PPI network analysis revealed that tumor protein P53, heat shock protein 90, Alpha Family Class A Member 1, AKT Serine/Threonine Kinase 1, Jun Proto-Oncogene, AP-1 Transcription Factor Subunit, Signal Transducer and Activator of Transcription 3, and Mitogen-Activated Protein Kinase 1 were the top ten most relevant targets. The results of the GO and KEGG analyses showed that the common targets of Panax ginseng and spermatogenesis were mainly involved in pathways related to cancer, p53, MAPK, lipid and atherosclerosis, and the human T-cell leukemia virus 1 infection signaling pathway. Molecular docking analysis suggested that potential targets for Panax ginseng, including quercetin, stigmasterol, inermin, ginsenoside Rg5 had the lowest docking energy for STAT3 and HSP90AA1. Conclusion: The present study identified the active components and probable molecular therapeutic mechanisms of Panax ginseng in enhancing spermatogenesis, providing a foundation for the widespread use of Panax ginseng in the male reproductive system.